Reabilitação urbana da Baixa Portuense - Qualidade Habitacional - Fátima Loureiro de Matos (2007)
In this article, we present a market study, whose goal it was to obtain a profile of the aspects that those who are potentially interested in living in Oporto's City Centre value when they are looking for housing. So as to accomplish this goal, the main concern guiding this study was the need to understand the aspirations and expectations that some groups hope to see fulfilled with their new homes. In the first part, we present a brief review of the concepts of urban regeneration/ rehabilitation. This is followed by the general characterization of the housing stock and the sociodemographic characteristics of Oporto's City Centre and finally, an analysis of the survey conducted on the potential demand for housing. A segment of the population, which uses this area for employment reason, purchases, leisure and the use of diverse services, was interviewed by questionnaire, during a street survey with 442 individuals.